Follow the Leader?: Optimism and Efficacy on Solo Journalism of Local Television Journalists and News Directors. (2nd January 2021) - Blankenship, Justin C.; Riffe, Daniel
ABSTRACT: This research article examined the perception of reporters and news managers at local television stations in the United States regarding "solo journalism." Solo journalism is the work practice in which a single reporter is expected to gather information, write, shoot video, and edit their news stories on their own. This is contrasted with a traditional news crew in which those tasks distributed among at least two workers, sometimes more. Based on theories of transformational leadership and self-concordance, it was hypothesized that news directors perceptions of solo journalism would impact their reporters. The study utilized data gathered from two separate, but linked surveys, one of news managers ( N = 159) and one of front-line journalists ( N = 222). The data indicated that journalists and news directors recognized that solo journalism will be integral to the future of television news. However, journalists are generally more pessimistic about the causes and benefits of solo journalism than news directors. Additionally, news directors admitted that they must utilize solo journalists differently than news crews. By matching the two samples by station, analysis suggested that the "optimism" of news managers toward solo journalism may impact the efficacy of the reporters that work for them.